Study on Fractional Differential Equations with Modified Riemann-Liouville Derivative via Kudryashov Method - Aksoy, Esin; Bekir, Ahmet; Cevikel, Adem C. (WALTER DE GRUYTER GMBH, 2019)
In this work, the Kudryashov method is handled to find exact solutions of nonlinear fractional partial differential equations in the sense of the modified Riemann-Liouville derivative as given by Guy Jumarie. Firstly, these fractional equations can be turned into another nonlinear ordinary differential equations by fractional complex transformation. Then, the method is applied to solve the space-time fractional Symmetric Regularized Long Wave equation and the space-time fractional generalized Hirota Satsuma coupled KdV equation. The obtained solutions include generalized hyperbolic functions solutions.
Keywords: exact solution; Kudryashov method; space-time fractional differential equation; modified Riemann-Liouville derivative; FINDING EXACT-SOLUTIONS; 1ST INTEGRAL METHOD; Engineering; Mathematics; Mechanics; Physics